Stage 3 Medication-related osteonecrosis of the jaw (MRONJ): successful conservative treatment with ozone therapy (Research, Society and Development, 2020)
Background: The medication-related osteonecrosis of the jaws is an uncommon severe complication following utilization of certain drugs, but its occurrence has great impact on the patient’s quality of life. Various treatment modalities are used to manage the lesions, including conservative and surgical procedures. Ozone (O3) therapy emerges as an alternative of non-invasive therapy that can benefit the affected patient without surgical risks, due to the potential of stimulate the activation and migration of fibroblasts in an injured area. Case presentation: This article reports the conservative treatment of a maxillary stage 3 medication-related osteonecrosis, in a partial edentulous patient previously treated with intravenous bisphosphonate for multiple myeloma, who had previous cardiac illness. Conclusion: The stage 3 medication-related osteonecrosis was successfully treated with ozone (O3) gas injection and irrigation with ozonated water, with full coverage of the bone and no suppuration or pain at the end of the treatment. No recurrence was seen after twelve months of follow-up.